Media Watch - Barrie Zwicker (Refuge: Canada's Journal on Refugees, 1982)
The majority of daily newspapers in addressed at some length by the Canada ignored the National Symposium as a whole such the Symposium on Refugee Determination. The majority of those that did not ignore it used wire copy. A tiny minority of papers sent staff reporters. Most coverage fell into two archetypes that characterize so much "news" in our papers.